ANALYSIS OF QUR'ANIC VERSES ON THE IDDAH PERIOD USING A HISTORICAL APPROACH (Application Case Study) - Pandu Wijaya; Kusnadi Kusnadi; Pathur Rahman (Jurnal Ushuluddin, 2026)
During the Jahiliyyah (pre-Islamic) period, women often experienced injustice regarding divorce and the waiting period following separation from their husbands. With the advent of Islam, clearer and more equitable regulations concerning iddah (the waiting period after divorce or widowhood) were established. Therefore, analyzing Qur'anic verses related to iddah through a historical approach is essential to understand how the Qur'an brought about social reform in the practices of that era. This study employs a qualitative method with a library research approach. The data were collected from various literary sources, including Qur'anic exegeses (tafsir), Islamic jurisprudence (fiqh) books, and scholarly studies relevant to the research topic. The analysis was conducted using a historical approach to understand the context in which the verses concerning iddah were revealed. The findings indicate that the regulations governing the iddah period were part of the social reforms introduced by Islam in response to pre-Islamic Arab customs that often disadvantaged women. The establishment of clear rules regarding iddah demonstrates Islam's commitment to protecting women's rights while also preserving the clarity of lineage within society.